Decorative painting on glass, ceramics & metal - Balchin, Judy (Search Press U.S.A, 1998)
Judy Balchin demonstrates, with clear step-by-step photographs, how easy and exciting it is to transform old bottles, flowerpots, plates, mugs, bowls and vases using simple decorative techniques. Learn how to paint on glass, how to decorate ceramics without using a kiln, and how to enhance metal objects. Techniques covered include free painting, outlining, stamping, sponging and stencilling using a ranger of paints. You can even adorn your designs with beads and stones. Projects include transforming flowerpots, plates, mugs, tiles, perfume bottles, bowls and vases. Templates are included showing all the designs featured in the book.